Pengembangan Media Pembelajaran Berbasis Audio Visual pada Materi Cerita Pendek untuk Siswa Kelas XI SMK - Simanjuntak, Amaya Tasha; Safina, Nila; Soraya, Ratna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2025)
This study aims to develop and evaluate the effectiveness of interactive audio-visual learning media for short story materials in 11th-grade vocational school students. Utilizing the Research and Development (R&D) method based on the Borg and Gall model, the research process involved data collection, planning, product development, initial field testing, revisions, and implementation. The findings indicate that the developed media was rated as "Highly Feasible" by both material and media experts, with respective approval percentages of 90.4% and 93%. The effectiveness test revealed a significant improvement in students' learning outcomes, achieving a "Highly Effective" score of 87.28%. These results demonstrate that audio-visual media can significantly enhance student engagement and comprehension of the material. Furthermore, the media facilitates a more interactive and immersive learning experience, promoting independent learning and critical thinking skills among students. This study highlights the potential of technology-enhanced learning tools in improving the overall quality of education in vocational schools.